Body Mass Index and Clinical Benefit of Fulvestrant in Postmenopausal Women with Advanced Breast Cancer. Issue 4 (July 2016) - Gevorgyan, Arpine; Bregni, Giacomo; Galli, Giulia; Ganzinelli, Monica; Martinetti, Antonia; Lo Vullo, Salvatore; Mariani, Luigi; Festinese, Fabrizio; Sottotetti, Elisa; de Braud, Filippo; Di Cosimo, Serena
Purpose: Obesity is a known risk factor for breast cancer and has been linked to increased risk of recurrence and death in breast cancer patients. Little is known about the predictive value of obesity. As endocrine therapy is widely used for breast cancer treatment worldwide, we aimed at correlating baseline body mass index (BMI) with clinical benefit derived from fulvestrant in postmenopausal women with advanced breast cancer. Methods: We analyzed consecutive patients treated with fulvestrant in our center between January 2009 and March 2015. Patients were categorized as normal (BMI 18.5-24.9 kg/m 2 ), overweight (BMI 25-29 kg/m 2 ) and obese (BMI >30 kg/m 2 ). The antitumor activity of fulvestrant was evaluated in terms of the clinical benefit rate (CBR). Results: Seventy-five consecutive patients matched the eligibility criteria for analysis. Fulvestrant was administered as first-line therapy in 4 (5%) cases, as second line in 27 (36%) and as third line and beyond in 44 (59%) cases. According to BMI, 44 (59%) patients were classified as normal weight, 19 (25%) as overweight, and 12 (16%) as obese. No difference in estrogen receptor expression was found in relation to BMI. CBR was 53% overall, but rose to 70.5% in normal-weight patients and dropped to 31.6% and 25% in overweight and obese patients, respectively (p<0.001). Conclusions: Increased BMI has a negative influence on treatment outcome. Even with the limitation of the relatively small sample size, it appears that patients of normal weight are 2.5-fold more likely to benefit from fulvestrant as overweight and obese patients.